E-013 Utility of the penumbra smart coil® system in treatment of intracranial aneurysms and malformations-interim analysis of the smart registry. (22nd July 2018) - Frei, D; Liu, K; Schirmer, C; Bohnstedt, B; Bellon, R; DeLeacy, R; Fiorella, D; Spiotta, A
Abstract : Introduction: Smart Coils are novel generation of embolic coils comprised of complex and WAVE shape properties with varying levels of softness to promote dense packing and durable long-term occlusion. We report results from interim analysis on utility of the Penumbra Smart Coil System in the treatment of a variety of intracranial vascular lesions, such as aneurysms and other abnormalities. Methods: SMART registry is a prospective and multi-center registry assessing treatment of intracranial aneurysms and other malformations. Procedures must implant at least 75% Smart, PC400, or POD coils to meet the registry criteria. SMART registry endpoints include retreatment through one-year follow-up, procedural device-related serious adverse events (SAE), occlusion status at immediate post-procedure, and at one- year follow-up. Results: The interim analysis from the first 500 consecutive subjects enrolled includes cerebral aneurysms (90.6%, 451/498), of which 31.0% were ruptured; arteriovenous malformations (1.4%); fistulae (4.6%); and other lesions (3.4%). At presentation, 70.8% of subjects were female, and the mean age was 60.0±13.3 years. The primary lesion locations are ACA (23.1%), ICA (37.6%), MCA (11.8%), posterior circulation (19.3%), and other locations (8.2%). Aneurysms were small (87.7%), large (12.1%), and giant (0.2%), with 64.2% (265/413) having a wide neck. The coil deployment time is defined as the time from the first coil deployed until the last coil detached. The median time of coil deployment is 16.0 min (IQR 8.0–32.0) and the median time of fluoroscopic exposure is 36.5 min (IQR 24.0–56.0). The mean number of coils deployed was 5.9±5.9. Stent-assisted coiling was performed in 29.8% of patients, whereas balloon-assisted coiling was performed on 19.4% of patients. The median packing density for all aneurysms was 29.5% (IQR 21.4–38.3). For all subjects, adequate occlusion at immediate post-procedure was achieved for 97.6% (483/495). In aneurysm subjects, class I and II Raymond Roy Occlusion was 79.7% (354/444) at immediate post-procedure, and 88.6% (124/140) at one year follow-up. The retreatment rate through one year follow-up was 3.8% (6/157). Procedural device-related SAE were observed in 3.2% subjects (16/500). Mortality within 24 hours of intervention was reported in 0.4% (2/496), and after 24 hours in 11.4% (21/185); no deaths were device-related. One-year follow-up data collection is ongoing. Conclusion: Initial results suggest that Smart Coil achieves adequate embolization in variety of neurovascular lesions. Disclosures: D. Frei: 2; C; Penumbra Inc. K. Liu: None. C. Schirmer: None. B. Bohnstedt: None. R. Bellon: None. R. DeLeacy: None. D. Fiorella: None. A. Spiotta: 2; C; Penumbra Inc.